Utilización de la plataforma educaplay en el desarrollo de destrezas en ciencias naturales de los estudiantes del sexto año de educación general básica paralelo “b” de la escuela Luis Aurelio González de la ciudad de Guaranda. período 2021-2022 - Bauz Baux, José Luis (2022)
He present investigatión was raised by the need to implement the technological, didactic tool that allows sharing a great variety of information, since the educaplay platform helps to plan interactive activities through the educational book and a pedagogical guide, providing the academic reinforcement of the students. , and managing to arouse the interest of the student with the use of new technological applications for integration into today's society. That is why the purpose of educational intervention work is to choose one of the various existing applications, whether in the educational field it should not only be limited to transmitting basic knowledge that is established in academic texts, but also make use of the tools where it allows the classes to be dynamic and fun that allow the development of skills - skills and build critical knowledge. The conclusion of the research is expressed in the need to incorporate innovative methods and resources that enable the increase of knowledge in schoolchildren through said application, as a key factor to achieve our purpose.